Identification of two flavin monooxygenases from an effluent treatment plant sludge metagenomic library - Singh, Ajit; Chauhan, Nar Singh; Thulasiram, H. V.; Taneja, Vibha; Sharma, Rakesh (Bioresource Technology, 2010)
Oxygenases are useful for the production of many industrially important molecules. Screening of an effluent treatment plant (ETP) sludge metagenomic library identified two clones encoding proteins, B1 and B2, with similarity to putative Flavin monooxygenases from Mesorhizobium loti and Sphingomonas wittichi, respectively. The deduced amino acid sequences show only 20% identity, but both have a paired Rossman fold and a flavin monooxygenase (FMO) motif. B1 and B2 appear to be members of the Flavin-containing monooxygenase and the Baeyer-Villiger monooxygenases subfamilies, respectively. When expressed in Escherichia coli, the two clones produced activities that oxidized indole to a mixture of indigo and indirubin pigments. These results suggest that B1 and B2 have potential as a biocatalyst in indigo/indirubin production. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Indigo; Indirubin; Metagenome; Metagenomic; Monooxygenase

Differential induction, purification and characterization of cold active lipase from Yarrowia lipolytica NCIM 3639 - Yadav, K. N. Sathish; Adsul, Mukund G.; Bastawade, Kulbhushan B.; Jadhav, D. D.; Thulasiram, H. V.; Gokhale, D. V. (Bioresource Technology, 2011)
The production, purification and characterization of cold active lipases by Yarrowia lipolytica NCIM 3639 is described. The study presents a new finding of production of cell bound and extracellular lipase activities depending upon the substrate used for growth. The strain produced cell bound and extracellular lipase activity when grown on olive oil and Tween 80, respectively. The organism grew profusely at 20 degrees C and at initial pH of 5.5, producing maximum extracellular lipase. The purified lipase has a molecular mass of 400 kDa having 20 subunits forming a multimeric native protein. Further the enzyme displayed an optimum pH of 5.0 and optimum temperature of 25 degrees C. Peptide mass finger printing reveled that some peptides showed homologues sequence (42%) to Yarrowia lipolytica LIP8p. The studies on hydrolysis of racemic lavandulyl acetate revealed that extracellular and cell bound lipases show preference over the opposite antipodes of irregular monoterpene, lavandulyl acetate. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Cell bound lipase; Cold active lipase; Extracellular lipase; Lavandulyl acetate; Oligomeric lipase

Andrographolide inhibits osteopontin expression and breast tumor growth through down regulation of PI3 Kinase/Akt signaling pathway - Kumar, S.; Patil, H. S.; Sharma, P.; Kumar, D.; Dasari, Sreekanth; Puranik, Vedavati G.; Thulasiram, H. V.; Kundu, G. C. (Current Molecular Medicine, 2012)
Breast cancer is one of the most common cancers among women in India and around the world. Despite recent advancement in the treatment of breast cancer, the results of chemotherapy to date remain unsatisfactory, prompting a need to identify natural agents that could target cancer efficiently with least side effects. Andrographolide (Andro) is one such molecule which has been shown to possess inhibitory effect on cancer cell growth. In this study, Andro, a natural diterpenoid lactone isolated from Andrographis paniculata has been shown to inhibit breast cancer cell proliferation, migration and arrest cell cycle at G2/M phase and induces apoptosis through caspase independent pathway. Our experimental evidences suggest that Andro attenuates endothelial cell motility and tumor-endothelial cell interaction. Moreover, Andro suppresses breast tumor growth in orthotopic NOD/SCID mice model. The anti-tumor activity of Andro in both in vitro and in vivo model was correlated with down regulation of PI3 kinase/Akt activation and inhibition of pro-angiogenic molecules such as OPN and VEGF expressions. Collectively, these results demonstrate that Andro may act as an effective anti-tumor and anti-angiogenic agent for the treatment of breast cancer.
Keywords: Andrographolide; angiogenesis and breast tumor; migration; osteopontin; PI 3 kinase

Way toward ``dietary pesticides'': molecular investigation of insecticidal action of caffeic acid against helicoverpa armigera - Joshi, Rakesh S.; Wagh, T. P.; Sharma, N.; Mulani, Fayaj A.; Sonavane, U.; Thulasiram, H. V.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Agricultural and Food Chemistry, 2014)
Bioprospecting of natural molecules is essential to overcome serious environmental issues and pesticide resistance in insects. Here we are reporting insights into insecticidal activity of a plant natural phenol. In silico and in vitro screening of multiple molecules supported by in vivo validations suggested that caffeic acid (CA) is a potent inhibitor of Helicoverpa armigera gut proteases. Protease activity and gene expression were altered in CA-fed larvae. The structure-activity relationship of CA highlighted that all the functional groups are crucial for inhibition of protease activity. Biophysical studies and molecular dynamic simulations revealed that sequential binding of multiple CA molecules induces conformational changes in the protease(s) and thus lead to a significant decline in their activity. CA treatment significantly inhibits the insect's detoxification enzymes, thus intensifying the insecticidal effect. Our findings suggest that CA can be implicated as a potent insecticidal molecule and explored for the development of effective dietary pesticides.
Keywords: Caffeic acid; Helicoverpa armigera; insecticidal activity; protease inhibitor

Systemic jasmonic acid modulation in mycorrhizal tomato plants and its role in induced resistance against alternaria alternata - Nair, A.; Kolet, Swati P.; Thulasiram, H. V.; Bhargava, S. (Plant Biology, 2015)
Tomato plants colonised with the arbuscular mycorrhizal (AM) fungus Glomus fasciculatum show systemic induced resistance to the foliar pathogen Alternaria alternata, as observed in interactions of other AM-colonised plants with a range of pathogens. The role of jasmonic (JA) and salicylic (SA) acid in expression of this mycorrhiza-induced resistance (MIR) against A.alternata was studied by measuring: (i) activity of enzymes reported to be involved in their biosynthesis, namely lipoxygenase (LOX) and phenylammonia lyase (PAL); and (ii) levels of methyl jasmonate (MeJA) and SA. Transcript abundance of some defence genes associated with JA and SA response pathways were also studied. Both LOX and PAL activity increased twofold in response to pathogen application to control plants. AM-colonised plants had three-fold higher LOX activity compared to control plants, but unlike controls, this did not increase further in response to pathogen application. Higher LOX activity in AM-colonised plants correlated with four-fold higher MeJA in leaves of AM-colonised plants compared to controls. Treatment of plants with the JA biosynthesis inhibitor salicylhydroxamic acid (SHAM) led to 50% lower MeJA in both control and AM-colonised plants and correlated with increased susceptibility to A.alternata, suggesting a causal role for JA in expression of MIR against the pathogen. Genes involved in JA biosynthesis (OPR3) and response (COI1) showed six- and 42-fold higher expression, respectively, in leaves of AM-colonised plants compared to controls. AM-colonised plants also showed increased expression of the SA response gene PR1 and that of the wound-inducible polypeptide prosystemin. Our results suggest that the systemic increase in JA in response to AM colonisation plays a key role in expression of MIR against A. alternata.
Keywords: Alternaria alternata; AM colonisation; induced resistance; Methyl jasmonate; salicylhydroxamic acid; Salicylic acid; Solanum lycopersicum

Acetone and methanol fruit extracts of terminalia paniculata inhibit HIV-1 infection in vitro - Durge, Ankita; Jadaun, Pratiksha; Wadhwani, Ashish; Chinchansure, Ashish A.; Said, Madhukar; Thulasiram, H. V.; Joshi, Swati P.; Kulkarni, Smita S. (Natural Product Research, 2017)
In this study, we report the in vitro anti-HIV1 activity of acetone and methanol extracts of fruit of Terminalia paniculata. Cytotoxicity tests were conducted on TZM-bl cells and peripheral blood mononuclear cells (PBMC), the CC50 values of both the extracts were 260g/mL. Using TZM-bl cells, the extracts were tested for their ability to inhibit replication of two primary isolates HIV-1 (X4, Subtype D) and HIV-1 (R5, Subtype C). The activity against HIV-1 primary isolate (R5, Subtype C) was confirmed using activated PBMC and by quantification of HIV-1 p24 antigen. Both the extracts showed anti-HIV1 activity in a dose-dependent manner. The EC50 values of the acetone and methanol extracts of T. paniculata were 10.3g/mL. The enzymatic assays were performed to determine the mechanism of action which indicated that the anti-HIV1 activity might be due to inhibition of reverse transcriptase (77.7% inhibition) and protease (69.9% inhibition) enzymes.

Camptothecin-producing endophytic bacteria from pyrenacantha volubilis hook. (Icacinaceae): a possible role of a plasmid in the production of camptothecin - Soujanya, K. N.; Siva, R.; Kumara, P. Mohana; Srimany, Amitava; Ravikanth, G.; Mulani, F. A.; Aarthy, T.; Thulasiram, H. V.; Santhoshkumar, T. R.; Nataraja, Karaba N.; Shaanker, R. Uma (Phytomedicine, 2017)
Background: Camptothecin (CPT), a quinoline alkaloid, is a potent inhibitor of eukaryotic topoisomerase I. Because of this property, several derivatives of CPT are used as chemotherapeutic agents. CPT is produced by several plant species belonging to the Asterid clade as well as by a number of endophytic fungal associates of these plants. In this study, we report the production of CPT by four bacterial endophytes and show the possible role of a plasmid in the biosynthesis of CPT. Methods: Endophytic bacteria were isolated from leaves, stems and fruits of Pyrenacantha volubilis Hook. (Icacinanceae). The bacterial isolates were purified and analyzed for production of CPT by ESI-MS/MS and NMR analysis. Bacterial identity was established based on the morphology and 16s rRNA sequence analysis. Crude extracts of the bacterial endophytes were evaluated for their cytotoxicity using colon cancer cell lines. The role of plasmid in the production of CPT was studied by purging the plasmid, using acriflavine, as well as reconstituting the bacteria with the plasmid. Results: Four bacterial isolates, Bacillus sp. (KP125955 and KP125956), Bacillus subtilis (KY741853) and Bacillus amyloliquefaciens (KY741854) were found to produce CPT in culture. Both based on ESI-MS/MS and NMR analysis, the identity of CPT was found to be similar to that produced by the host plant. The CPT was biologically active as evident by its cytotoxicity against colon cancer cell line. The production of CPT by the endophyte (Bacillus subtilis, KY741853) attenuated with sub-culture. A likely role of a plasmid in the production of CPT was established. A 5 kbp plasmid was recovered from the bacteria. Bacterial isolate cured of plasmid failed to produce CPT. Conclusion: Our study implies a possible role of a plasmid in the production of CPT by the endophytic bacteria and opens up further work to unravel the exact mechanisms that might be involved.

Role of jasmonate in modulation of mycorrhizae-induced resistance against fungal pathogens - Nair, Aswathy; Thulasiram, H. V.; Bhargava, Sujata (Methods in Molecular Biology, 2020)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Symbiotic association of plants with arbuscular mycorrhizal (AM) fungi brings about changes in levels of the phytohormone jasmonate (JA) in root and shoot tissues of a plant. The enhanced JA levels not only play a role in controlling the extent of AM colonization but are also involved in the expression of mycorrhizal-induced resistance (MIR) against pathogens. We describe a method used to study the levels of a volatile jasmonate derivative, methyl jasmonate (MeJA), in tomato plants colonized by AM fungi and in response to subsequent attack by the foliar pathogen Alternaria alternata.

Diversity assessment of Gloriosa superba accessions from Western Ghats of India based on morphological traits, ISSR markers and metabolite content - Mahajan, Yogesh A.; Shinde, Balkrishna A.; Mulani, Fayaj A.; Gade, Akshay B.; Kasodekar, Amol K.; Thulasiram, H. V.; Kadoo, Narendra Y.; Nikam, Tukaram D. (Journal of Applied Research on Medicinal and Aromatic Plants, 2022)
Gloriosa superba L. (glory lily) is a medicinally and horticulturally important plant used as a commercial source of the alkaloid colchicine. The Western Ghats in India is mostly unexplored for the morphological, genetic, and metabolite diversity of the species. In the current study, three methodologies were employed to assess the diversity among 50 established accessions of G. superba collected from several locations in the Western Ghats. The morphological analysis revealed that, among the studied traits, seed yield per vine and dry seed weight per 100 seeds for the established accessions were the most diverse traits. The former exhibited a significantly positive correlation with four vegetative and five yield traits. The first three principal components showed nine traits contributing to the variation. Intra-specific molecular variation based on inter simple sequence repeat markers distributed the accessions in three clusters with high polymorphism and low genetic diversity indices. Liquid chromatography high-resolution mass spectrometry analysis revealed significant variation among the screened accessions for colchicine content in tuber and seed tissue. Interestingly, an unexplored tissue, pod shell, was found to contain significantly high colchicine, which could be explored for commercial colchicine extraction. The morphogenetic and metabolite variation revealed by the study would be useful to develop elite varieties to expand the cultivation of glory lily across the country, fulfilling the increasing demand for colchicine and providing remunerative income to the farmers.
Keywords: Colchicine; Genetic diversity; Gloriosa superba; Metabolite diversity; Morphological diversity; Western Ghats

Bacopa monnieri reduces Tau aggregation and Tau-mediated toxicity in cells - Dubey, Tushar; Kushwaha, Preeti; Thulasiram, H. V.; Chandrashekar, Madhura; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2023)
Alzheimer's disease is a neurodegenerative disease characterized by progressive memory loss and behavioral impairments. In the present study, the ethanolic extract of Bacopa monnieri was studied for its potency to inhibit Tau aggregation and rescuing of the viability of Tau-stressed cells. Bacopa monnieri was observed to inhibit the Tau aggregation in vitro. The cells exposed to Bacopa monnieri were also observed to have a low level of ROS and caspase-3 activity. The immunoblot and immunofluorescence analysis showed that Bacopa monnieri acts as an antioxidant and restored the Nrf2 levels in Neuro2a cells. Bacopa monnieri treatment to Neuro2a cells was observed to reduce the phospho-Tau load in formaldehyde-stressed cells. Furthermore, the treatment of Bacopa monnieri reduced the phosphorylation of GSK-3 beta in formaldehyde-stressed cells. Ran and NUP358 are the key proteins involved in nuclear transport. It was observed that formaldehyde treatment impaired the nuclear transport by missorting the NUP358 arrangement in Neuro2a cells. On the contrary, Bacopa monnieri treatment restored the NUP358 arrangement in cells. The overall results of the present study suggested that Bacopa monnieri could be considered a potent herb against Tau phosphorylation and Tau aggregation, which projects it as a promising formulation for Alzheimer's disease.
Keywords: Bacopa monnieri; GSK-3 beta; Nrf2; Nuclear transport; NUP358; Tau Aggregation; Tau phosphorylation